Factors Influencing Customer Satisfaction With Demand for Make Up Artist (MUA) Services - Fortuna, Salsa Dwi; Mustafa, Sry Wahyuny; Muhani, Mustafa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Customer satisfaction is an element in achieving the goals of Kya Stephanie Make Up salon and maintaining income in a company. Various factors to obtain customer satisfaction, and in service quality is needed to obtain customer satisfaction. In this study describes the influence of customer satisfaction, on the demand for make up services at Kya Stephanie salon with the number of data collection techniques through the distribution of questionnaires to 40 respondents who arehave used MUA services as the population and sample in this study.The results of this study indicate that price on consumer demand itself has an influence but is not significant and Customer Satisfaction has a positive impact on the Consumer Demand variable but in testing the level of accuracy and significance of these two variables do not have an influence and are significant. While Social Media on Consumer Demand among MUA service users has an influence but is not significant. These results illustrate that the role of social media certainly has an influence on online content references that allow MUA and consumers themselves to share